2022
DOI: 10.1002/bit.28246
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends using natural polymeric nanofibers as supports for enzyme immobilization and catalysis

Abstract: All the disciplines of science, especially biotechnology, have given continuous attention to the area of enzyme immobilization. However, the structural support made by material science intervention determines the performance of immobilized enzymes. Studies have proven that nanostructured supports can maintain better catalytic performance and improve immobilization efficiency. The recent trends in the application of nanofibers using natural polymers for enzyme immobilization have been addressed in this review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 157 publications
0
8
0
Order By: Relevance
“…It has been demonstrated that the bioactive ingredients embedded in electrospun fibers exhibited enhanced stability and bioavailability, achieving targeted delivery and sustained release [ 43 , 44 , 45 ]. With respect to immobilization, an electrospun fiber mat was primarily used as the matrix for immobilizing enzymes to improve their stability and reusability [ 46 , 47 ].…”
Section: Electrospinning For Probiotic Stabilizationmentioning
confidence: 99%
“…It has been demonstrated that the bioactive ingredients embedded in electrospun fibers exhibited enhanced stability and bioavailability, achieving targeted delivery and sustained release [ 43 , 44 , 45 ]. With respect to immobilization, an electrospun fiber mat was primarily used as the matrix for immobilizing enzymes to improve their stability and reusability [ 46 , 47 ].…”
Section: Electrospinning For Probiotic Stabilizationmentioning
confidence: 99%
“…[1][2][3] The remarkable specific surface area and high porosity make electrospun nanomaterials highly attractive as ultrasensitive sensors and of increasing importance in other nanotechnological applications. [4][5][6][7][8] Electrospun polymer nanofibers can be used in sensor applications as their effective sensing surface area increases with decreasing fiber diameter. [9][10][11][12] The tunable polymer composite chemistry and functionality of the fiber material allow for exploring different applications, i.e., filtration media for wastewater management, 13 photocatalytic degradation of pollutants, 14 fire protection materials, 15 volatile organic compounds and oxidative gases.…”
Section: Introductionmentioning
confidence: 99%
“…Various biomaterials have been employed in tissue engineering, taking the form of polymeric scaffolds and biological scaffolds. A significant research challenge lies in creating tissue-like scaffolds at the nanoscale [1], [2]. The extracellular matrix (ECM) can be defined as a multiplex system with various components, and reproducing its intricate composition and functions for tissue engineering is a formidable task [3].…”
Section: Introductionmentioning
confidence: 99%